2014
DOI: 10.1053/j.gastro.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir-Like Inhibitors of NS5A Block Early Biogenesis of Hepatitis C Virus–Induced Membranous Replication Factories, Independent of RNA Replication

Abstract: Highly potent inhibitors of NS5A, such as daclatasvir, block replication of HCV RNA at the stage of membranous web biogenesis-a new paradigm in antiviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
153
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 140 publications
(171 citation statements)
references
References 52 publications
14
153
1
3
Order By: Relevance
“…Electron microscopy analyses suggest that NS5A-positive structures correspond, in part, to double membrane vesicles, which are a hallmark of the membranous HCV replication factory, designated membranous web (52). A NS5A "cluster" phenotype similar to that of the PW turn mutants was previously found in cells treated with NS5A or Cyp inhibitors (46,52,53), as well as in PI4KIII␣ knockdown cells. This phenotype was shown to correspond to lipid droplets or aberrant double membrane vesicles, respectively (47).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Electron microscopy analyses suggest that NS5A-positive structures correspond, in part, to double membrane vesicles, which are a hallmark of the membranous HCV replication factory, designated membranous web (52). A NS5A "cluster" phenotype similar to that of the PW turn mutants was previously found in cells treated with NS5A or Cyp inhibitors (46,52,53), as well as in PI4KIII␣ knockdown cells. This phenotype was shown to correspond to lipid droplets or aberrant double membrane vesicles, respectively (47).…”
Section: Discussionmentioning
confidence: 73%
“…9B, right column). This altered phenotype correlated with a strong accumulation of large structures where NS5A is present, reminiscent of the cluster distribution in cells treated with NS5A and Cyp inhibitors (46,52,53). Notably, the proportion of cells with the cluster phenotype varied from 24 to 67% for I315G and P314A mutants, respectively, compared with 5% for WT (Fig.…”
mentioning
confidence: 78%
“…To do this we utilized a chimeric virus that expressed Renilla luciferase (J6/JFH-1-Rluc) (Jones et al, 2007) mechanism of action of DCV at early stages in the virus life cycle has been recently reported (Berger et al, 2014) and proposed to involve disruption of membranous web formation.…”
Section: Pi3k Activity Is Required For Hcv Genome Replicationmentioning
confidence: 99%
“…NS5A has no known enzymatic activity and to date the exact mechanism(s) of action of these inhibitors and indeed the exact functions of NS5A remain unclear. In this issue of Gastroenterology, Berger et al 5 report that NS5A inhibitors interact with NS5A and block formation of the "membranous web" (MW) that houses HCV RNA replication, independent of effects on HCV RNA replication. Furthermore, the authors present evidence that DCV derivatives interact with NS5A dimers and moderately impair functional interaction of NS5A with phosphatidylinositol-4 kinase IIIa (PI4KIIIa) that stimulates local accumulation of PI4-phosphate (PI4P) at sites of HCV RNA replication.…”
Section: Hcv Ns5a Inhibitors Disrupt Replication Factory Formation: Amentioning
confidence: 99%
“…Finally, it has been suggested that NS5A inhibitors may disrupt interactions of NS5A with HCV RNA, other viral proteins, and/or host factors that are coopted by NS5A during the HCV life cycle. The study of Berger et al 5 comprehensively addresses many of these properties of NS5A inhibitors and uniquely addresses their effects on NS5A-induced PI4P accumulation and HCVinduced membrane rearrangements.…”
Section: Hcv Ns5a Inhibitors Disrupt Replication Factory Formation: Amentioning
confidence: 99%